Karakteristik Indonesia Investment Authority (INA) Sebagai Sovereign Wealth Fund dalam Hukum Investasi: Studi Komparatif dengan China Investment Corporation (CIC) - Rijaal, Muhammad (LPPM Institut Pendidikan Nusantara Global, 2025)
The Indonesian Investment Authority (INA) is a sovereign investment institution established to strengthen national development financing through strategic partnerships with foreign investors. In the context of investment law, the INA represents a new actor within Indonesia's legal framework—namely, the sovereign wealth fund (SWF)—which has received limited scholarly attention, particularly regarding its legal design and institutional governance. This study addresses this research gap by analyzing the characteristics, institutional structure, and governance of the INA, as a SWF and comparing its characteristics with that of the China Investment Corporation (CIC), the SWF of the People's Republic of China. Using a normative and comparative approach, this study found that although INA and CIC have different forms of legal entities, INA operates as a sui generis legal entity that is directly accountable to the President and the Supervisory Board, while CIC is in the form of a Limited Liability Company with a company-oriented governance model. Although different from the form of legal entities, both have governance that applies the principles of SWF management regulated in the Santiago Principle so that they remain accountable. These findings contribute to the development of Indonesia's investment law by emphasizing the importance of institutional design that balances investment autonomy with public accountability, thereby increasing investor confidence and the effectiveness of national development financing.